MOTIVASI INDONESIA MENERAPKAN PROGRAM HIGHLY SENSITIVE LIST TRACK TERHADAP PRODUK EKSPOR PERTANIAN DARI INDONESIA KE TIONGKOK TAHUN 2007-2014 - Galih Lintang Dwinda; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describe the motivation Indonesia implemented highly sensitive list track programs for export of agriculture product from Indonesia to Tiongkok in 2007-2014. This program was implemented when Indonesia and Tiongkok Governments was deal about ASEAN-China Free Trade Area. ACFTA are agreement that have purpose to make free trade between Tiongkok and ASEAN state.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the role of international organization for migration in antisipated human trafficking in Indonesia. The theories applied in this research are neo liberalism perspective with comparative advantage theory.The conclusion of the research about the motivation Indonesia implemented highly sensitive list track programs for export of agriculture product from Indonesia to Tiongkok are because implementation tariff for export of agriculture product from Indonesia to Tiongkok. In order that, when ACFTA was implemented the tariff export of agriculture product from Indonesia to Tiongkok can be decrease to 5 until 0%.Key words: motivation, program, track and export.